2016
DOI: 10.1590/s0102-053620160408
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfoagronômica preliminar de acessos de pimentas cumari

Abstract: RESUMOA pimenta cumari, Capsicum baccatum var. praetermissum e C. baccatum var. baccatum, é uma espécie semidomesticada, endêmica das regiões Sudeste e Centro-Oeste do país. Apesar da sua importância econômica, principalmente para a agricultura familiar, e da sua ampla variabilidade, ainda não existe uma cultivar dessa espécie disponível no mercado brasileiro. Este trabalho teve como objetivo avaliar acessos de pimenta cumari do Banco de Germoplasma de Capsicum da Embrapa Hortaliças com base em características… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
(6 reference statements)
1
7
0
3
Order By: Relevance
“…Nitrogen fertilization positively affected plant growth without altering antioxidant content. Regarding the growth of pepper genotypes, in general, the results of the present study are similar to those reported by Araújo et al (2018) and Ferraz et al (2016). In pepper plants, plant height and stem diameter are strongly influenced by nitrogen fertilization (Oliveira et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nitrogen fertilization positively affected plant growth without altering antioxidant content. Regarding the growth of pepper genotypes, in general, the results of the present study are similar to those reported by Araújo et al (2018) and Ferraz et al (2016). In pepper plants, plant height and stem diameter are strongly influenced by nitrogen fertilization (Oliveira et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In C. chinense, the flowering time is 95 days (Domenico et al, 2012). In C. praetermissum, flowering and fruit ripening time are 81 and 101 days, respectively (Ferraz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the species of this genus are consumed by a quarter of the world population, and present a highly diversified market, extending from the commercialization for in natura consumption and homemade canned sauces to the exportation of industrialized products. It is utilized in pharmaceutical and cosmetic products, besides its use as ornamental plants (Ferrão et al, 2011;Ferraz et al, 2016;Neitzke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…importance in income generation for small farmers (Rêgo et al 2015;2018). The characterization and evaluation of conserved genotypes constitute a step of great importance for the immediate utilization of the species in breeding programs (Costa et al, 2015;Ferraz et al, 2016;Rêgo et al, 2011). It is fundamental the detection of duplicate plants in the germplasm banks (Gonçalves et al, 2008;Laurentin, 2009;Rêgo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sustent., 2020, vol. 7, n. 17, p. 1165-1174. melhoramento adotar estratégias de uso do potencial ornamental de pimentas (Neitzke et al, 2010;Ferraz et al, 2016).…”
Section: Introductionunclassified